PSYCHOLOGICAL AND PEDAGOGICAL TRAINING OF THE TEACHER HIGHER TECHNICAL SCHOOL: PROBLEMS AND PROSPECTS OF DEVELOPMENT - Бабак, В. П.; Лузік, Е. В. (Proceedings of National Aviation University (archive), 2021)
The problems of shortage of psychological and pedagogical staff of technical universities are considered. The reasons for the need to restructure the system of postgraduate education of higher technical school in the direction of training a new generation of scientific and pedagogical staff with a high level of professionalism, methodological and general culture, innovative creative style of analytical thinking are analyzed. The ways of solving the set problems in the form of problem-activity concept of postgraduate education in higher technical educational establishments are determined.